Application of Ranganathan's Five Laws in Collection Management at the Indonesian Academy of Pharmacy Library in Yogyakarta - Al Ghiffary, Ghalib Muhammad Syukri; Zain, Labibah (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2025)
Background of the study: Vocational academic libraries face challenges in implementing ideal collection development principles due to resource constraints, creating a gap between theory and practice. Purpose: To analyze the application of Ranganathan's Five Laws as an adaptive framework for collection management in the small-scale AFIYO Library. Method: A qualitative study with a single case design, using in-depth interviews, participant observation for 10 weeks, and document analysis. Data were analyzed through thematic analysis with source triangulation. Findings: (1) Collaboration with lecturers improved collection relevance by 71%; (2) Limited budget (IDR 10 million/year) triggered strict selection focused on D3 Pharmacy curriculum needs; (3) Multi-channel promotion strategies enhanced new collection visibility; (4) OPAC and personal service combination created contextual efficiency; (5) Networking served as alternative growth strategy replacing acquisition. Conclusion: This study recontextualizes Ranganathan's Five Laws for resource-constrained libraries and provides an adaptable collection policy framework for similar vocational libraries. Keywords: Collection Development, Ranganathan's Five Laws, Vocational Libraries, Collection Management, Information Access --------------------------------------------------------------------------------------------------------------------------------------------------------------------- ABSTRAK   Penerapan Lima Hukum Ranganathan dalam Manajemen Koleksi di Perpustakaan Akademi Farmasi Indonesia Yogyakarta Latar Belakang: Perpustakaan akademik vokasional menghadapi tantangan implementasi prinsip pengembangan koleksi ideal akibat keterbatasan sumber daya, menciptakan kesenjangan antara teori dan praktik Tujuan: Menganalisis penerapan Lima Hukum Ranganathan sebagai kerangka kerja adaptif untuk manajemen koleksi di Perpustakaan AFIYO yang berskala kecil. Metode: Penelitian kualitatif dengan studi kasus tunggal, menggunakan wawancara mendalam, observasi partisipan selama 10 minggu, dan analisis dokumen. Data dianalisis melalui teknik analisis tematik dengan triangulasi sumber. Temuan: (1) Kolaborasi dengan dosen meningkatkan relevansi koleksi hingga 71%; (2) Anggaran terbatas (Rp 10 juta/tahun) memicu seleksi ketat yang berfokus pada kebutuhan kurikulum D3 Farmasi; (3) Strategi promosi multi-saluran meningkatkan visibilitas koleksi baru; (4) Kombinasi OPAC dan layanan personal menciptakan efisiensi kontekstual; (5) Jejaring kerja sama menjadi strategi pertumbuhan alternatif pengganti akuisisi. Kesimpulan: Studi ini merekontekstualisasi Lima Hukum Ranganathan untuk perpustakaan terbatas sumber daya dan menyediakan kerangka kebijakan koleksi yang dapat diadaptasi oleh perpustakaan vokasional sejenis. Kata Kunci: Pengembangan Koleksi, Lima Hukum Ranganathan, Perpustakaan Vokasional, Manajemen Koleksi, Akses Informasi